PENGARUH VARIASI MUTU BETON PADA BENDA UJI BALOK BETON NORMAL DENGAN MENGGUNAKAN METODE NON DESTRUCTIVE TEST - Kushariyanto Kushariyanto; Christin Remayanti Nainggolan; Siti Nurlina (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
This research aims to know the relationship of the pulse velocity to compression strength with a variation of the quality of the concrete based on the ultrasonic pulse velocity. This research uses the PUNDIT PL-200 to do the process of analysis of concrete density based on the pulse velocity from the UPV. From UPV testing in this research showed that each quality and each method has a strong connection of the same compression strength and velocity. This is indicated by rising the velocity graph as the quality of the concrete itself increases. From this research also gained comparisons between the three methods, which is between direct and semi-direct methods, direct and indirect methods, as well as semi-direct and indirect methods.